Pattern of Antibiotic Sensitivity and Resistance in Various Cases of Sepsis in a Mixed Intensive Care Unit set up in a Tertiary Hospital - Sharma, Sagun; Adhikari, Milan; Basnet, Anisha; Khadka, Shishir; Das, Ram; Bhatta, Ashish (Journal of Nepalgunj Medical College, 2023)
Introduction: Sepsis has been shown to be one of the critical reasons for Intensive Care Unit admissions of patients for which early and empirical use of antibiotics have been used. Antibiotics resistance is becoming a matter of serious concern, especially in developing countries like ours. In this study, all the cases those were diagnosed with sepsis and had culture positive results for bacteria have been evaluated. Aims: To find out the common organisms responsible for sepsis in patients admitted to the Intensive Care Unit and to know the antibiotic sensitivity/resistance patterns. Methods: The study was done from May 2022 to April 2023 in mixed Intensive Care Units on the clinical isolates from blood, urine, sputum, endotracheal tube aspirate, central venous catheter tips and wound swabs and those were sent to microbiology department for culture and sensitivity. All the organisms were identified morphologically and biochemically and antibiotic susceptibility pattern was determined by standard laboratory procedure. Results: We took a total of 102 samples in which organisms were isolated. The most frequently isolated bacteria were Klebsiella (24.91%) followed by Staphylococcus aureus (24.5%), both were sensitive to Doxycycline and Tazobactam-piperacillin in most cases. Other organisms isolated were Escherichia coli (15.69%), Streptococcus (9.8%), Pseudomonas (8.82%), Acinetobacter (6.86%), Enterobacter species (3.92%) and Proteus (0.98%). Azithromycin was found to be the most resistant drug followed by Amoxycillin/clavulanic acid and Levofloxacin. Conclusion: Klebsiella was found to be the most prevalent cause of sepsis in ICU. Most of the frequently isolated pathogens were resistant to Beta lactamase inhibitors, Cephalosporins and Quinolones. Regular surveillance of antibiotic susceptibility pattern is very important for setting a guideline to the clinician in choosing an appropriate therapy for patients with sepsis.